Copper-nickel doped LTA zeolite as a high- efficiency methanol oxidation reaction catalyst in alkaline solution. (6th July 2021) - Qian, Kun; Li, Li; Chen, Peng; Xiu, Yang; E, Yifeng; Gies, Hermann
Abstract: An improved method is used to obtain a highly active copper-nickel doped LTA zeolite composite material. The method is combined by the in-situ synthesis of copper and nickel in the LTA zeolite framework and electrochemical reducing ions to monodisperse elemental substances which are restricted domain on the opening window pores of the zeolite. Especially in the case of high methanol concentration, this electrochemically reduced material exhibits good catalytic activity for methanol oxidation reaction (MOR) in an alkaline solution which is due to the excellent resistance to catalyst poisoning. Even if the methanol concentration reaches 25M, the catalytic activity of this material is still raising. Without precious metals in this kind of methanol oxidation reaction catalyst, it will likely greatly cut down the cost of methanol fuel cells to further improve the energy density of methanol fuel cell under high concentration. Highlights: In-situ synthesis for Cu and Ni on the LTA zeolite surface. Electrochemical reducing ions to monodisperse substances. Substances restricted on zeolitic opening window pores. Good catalytic activity for methanol oxidation reaction. Low cost methanol fuel cells under high concentration.